2022
DOI: 10.1002/aff2.33
|View full text |Cite
|
Sign up to set email alerts
|

Culturing live foods for fish larviculture using non‐microalgal diet: The role of waste‐generated bacteria and selected commercial probiotics—A review

Abstract: Condensed suspension of live microalga cells, for example, Chlorella vulgaris, Nannochloropsis oculata and Tetraselmis tetrathele is often utilized as diets for mass production of live food resources, that is, rotifers, copepods, cladocerans and Artemia. These live food resources are essential for fish larviculture in hatcheries. However, the production of sufficient microalgae is costly, laborious and fragile, and thus require costeffective and stable production technologies, especially for the emerging count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…Several studies have sought alternatives to live food production, and Kagali et al (2022) suggested the biofloc system as an alternative system, with the potential to avoid enrichment necessities and microbiological contamination. Therefore, the direct use of bioflocs, such as a larviculture system, is promising because of the stability of water quality parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have sought alternatives to live food production, and Kagali et al (2022) suggested the biofloc system as an alternative system, with the potential to avoid enrichment necessities and microbiological contamination. Therefore, the direct use of bioflocs, such as a larviculture system, is promising because of the stability of water quality parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Rotman et al (2011) reported in their study that the addition of commercial probiotics did not affect rotifer population density. The action of probiotics is thought to follow species-and strain-specific properties (Cha et al, 2013;Kagali et al, 2022;Lamari et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the rotifers could obtain some nutritional ingredients through direct ingestion of microparticles (ash, organic debris, etc.) in the absence of microalgae or at low microalgae density (Kagali et al, 2022; Ogello et al, 2018; Quy et al, 2018; Rothhaupt, 1990). CME is rich in nutrients, such as PUFAs (Chen et al, 2006; Das et al, 2009; Deng et al, 2020; Wang et al, 2003; Watanabe et al, 1983); therefore, CME is likely to be able to improve the nutritional status of rotifers.…”
Section: Introductionmentioning
confidence: 99%